Meja Getar dengan Sistem Tiga Penggerak Pneumatik untuk Skala Laboratorium - Dedi Suryadi; Hade Syamitra; Ahmad Fauzan; Novalio Daratha; Indra Agustian (Department of Mechanical Engineering, Universitas Andalas, 2021)
This study aims to develop a laboratory scale shaking table that can simulate vibrations level by using PLC as controller. Mechanism of the shaking table consists of cylinder pneumatic drive system, where the movement comes from 3 of pneumatic cylinders connected to the solenoid vale later controlled using PLC OMRON CP1L. Therefore, it can produce vertical and horizontal translational movements. Dynamic response can be obtained by varying frequency of 1 Hz, 2 Hz, 3 Hz, 4 Hz, and 5 Hz. Moreover, loads are also varied by 1kg, 2kg and no load. The results of this study indicate that the shaking table is successfully developed that can perform 2 types of translational movements in the vertical and horizontal direction that operate at a frequency of 1 Hz to 5 Hz with maximum load of 2 kg. Amplitude of shaking table increases by decreasing frequency input and loading value. Also, amplitude increases by decreasing value of the valve openings.